Pelatihan Pembuatan Media Pembelajaran Daring Dengan Menggunakan Aplikasi Open Broadcaster Software Studio Untuk Memaksimalkan Literasi Digital Pada Guru-Guru Sdn 1 Nagrikidul (Current Research in Education: Conference Series Journal, 2023)
Learning during this pandemic requires carrying out online following government instructions in the Circular Letter of the Ministry of Education and Culture No. 1 of 2020. For learning activities to continue, there are two modes or methods that can be used, namely asynchronous and synchronous. In carrying out this activity at SDN 1 Nagrikidul, it turns out that it is still not optimal both in making learning media videos and in conducting online activities. Because of this problem, the researcher intends to make Open Broadcaster Software Studio application training for teachers to maximize online activities or create learning media. In its implementation, researchers used two methods of data collection, namely primary data and secondary data. When conducting the training activities, researchers distributed pre-test survey questionnaires and it was found that all of the training participants had heard of the term OBS and observed people using OBS but in using it, participants still did not understand the features in this OBS application. After conducting the training, it was found that 100% of the trainees felt that their ability to use the OBS application had increased and made the trainees able to optimize the use of OBS.